Corrosion Behavior and Mechanical Properties as a Function of Reverted Austenite in Laser Powder Bed Fusion 18Ni Maraging Steel - Conde, Fabio Faria; da Cruz Passos, João Gabriel; Calderón-Hernandez, José Wilmar; Sharifi, Saham Sadat; Buzolin, Ricardo Henrique; Jardini, André; Oliveira, Marcelo Falcão; Avila, Julian [UNESP] (Springer Nature, 2025)
Maraging steels like 18Ni-300 offer high strength and toughness due to a low-carbon martensitic matrix with nanosized intermetallic precipitates. Their weldability makes them ideal for additive manufacturing, particularly laser-based powder bed fusion (L-PBF). While L-PBF enhances tooling durability, components face stress, wear, and corrosion challenges, requiring a deeper understanding of structure–property correlations to optimize performance. This alloy can undergo austenite reversion during intercritical or aging, depending on the time and temperature of heat treatment. The formation of reverted austenite implies a depletion of some chemical elements in the martensite matrix, such as Ni in the maraging steel, which could, in theory, lead to a loss of corrosion resistance. This study investigates the influence of reverted austenite on the mechanical and corrosion properties of 18Ni maraging steel produced by L-PBF. To control the volume fraction of reverted austenite, samples were subjected to intercritical heat treatments at 610 and 650 °C for varying durations. While the sample with the highest austenite fraction (30.8%) showed poor toughness, a modest 7.5% volume fraction of finely dispersed austenite was sufficient to significantly enhance fracture toughness, indicating that the austenite's stability and morphology are more critical than its bulk volume. We found a clear inverse correlation between austenite content and corrosion resistance in both NaCl and H2SO4 environments. The corrosion potential (Ecorr) decreased from − 637 mV in the as-built sample (3.0% austenite) to − 684 mV in the sample containing 30.8% austenite. This degradation is attributed to micro-galvanic coupling between the Ni-enriched austenite and the Ni-depleted martensitic matrix.